EXPERIMENTAL STUDY OF POLYSULFANE STABILITY IN GASEOUS HYDROGEN SULFIDE - Migdisov A.A.; Suleimenov O.M.; Alekhin Yu.V. (My University, 1998)
The solubility of sulfur in gaseous hydrogen sulfide has been studied in the H2S-S system. Experiments were carried out at temperatures between 50 and 290°C and pressures up to 200 bars. The experimentally determined concentrations of sulfur in the gas phase are 6–7 orders of magnitude higher than the corresponding concentrations calculated for a system free of hydrogen sulfide. The results of experiments show significant interaction between S and H2S. These interactions can be of two kind: solvation by hydrogen sulfide (solubility), as with formation of new stable gaseous chemical compounds, like polysulfanes (chemical reaction). The data obtained can be reasonably well described by the formation of a H2S · S compound. Thermodynamic parameters for polysulfanes and equilibrium compositions of the S-H2S system have been calculated ab initio for the experimental conditions. At temperatures above 170°C, results (of calculations) are in good agreement with experimental data, although the difference between the calculated and experimental mole fraction of the sulfur in the gas phase reaches 2 orders of magnitude at 125–170°C. It is theorized that sulfur solubility in gaseous H2S is related to two main chemical reactions, dominated in the different temperature ranges: sulfur solvation by H2S (125–170°C) and polysulfane formation (200–290°C).